Adsorption Studies of Rice Husk-Based Silica/Carbon Composite - Wara Dyah Pita Rengga; Wahyudi Budi Sediawan; Nadya Alfa Cahaya Imani; Harianingsih Harianingsih; Kega Amalania Salsabiil (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Rice husk as a by-product of the rice milling process is a material that can still be processed to be a product that can be used in various applications. The potential for the commercialization ofrice husks is still hampered by its low economic value. By using the heating method using an inert gas, rice husk can be converted into a composite which contains mostly silica and carbon, a wellknown component with excellent adsorbent properties. This aimed to study the preparation of rice husk-baased silica/carbon composite and its adsorption behavior. In this research, the utilization of rice husk into silica/carbon composites was done by using three different methods. Common heating under temperature of 800 oC, heating process under temperature of 800 oC using furnace equipped with inert gas, and heating process under temperature of 800 oC using furnace equipped with inert gas with addition of glucose solution were carried out in order to obtain three different kinds of composite. Analysis and characterization using were performed to observe the properties of the composites. As the result, from Fourier Transform Infra-Red and X-Ray diffraction characterizations, silica/carbon composites were successfully made as both of carbon and amorphous silica spectra appeared in the result. Furthermore, composite made under temperature of 800 oC using furnace equipped with inert gas with addition of glucose solution has the highest adsorption capacity and Langmuir’s model adsorptive behavior with R2 value of 0.935.